Pattern and predictors of soil-transmitted helminth reinfection among aboriginal schoolchildren in rural Peninsular Malaysia - Al-Mekhlafi, M.H.; Surin, J.; Atiya, A.S.; Ariffin, W.A.; Mahdy, A.K.M.; Abdullah, H.C. (2008)
Data on soil-transmitted helminth (STH) infections and reinfection among Orang Ash (aborigine) schoolchildren and their nutritional and socioeconomic status were analyzed to investigate the pattern and the possible predictors of STH reinfection. In this longitudinal study, 120 (60 males and 60 females) Orang Ash primary schoolchildren aged 7-12 years and living in remote areas in Pos Betau, Kuala Lipis, Pahang were screened for the presence of STH using modified cellophane thick smear and Harada Mori techniques. The overall prevalence of ascariasis, trichuriasis and hookworm infections were 65.8, 97.5 and 10.8, respectively. After complete deworming with a 3-day course of 400 mg/daily of albendazole tablets, children were re-examined at 3 and 6 months from baseline. The reinfection rate, by one or more of STH species, at 3 months after deworming was high (49.5) while 79.6 of the children were reinfected at 6 months after deworming. Logistic regression analyses showed that females, stunted children and those living in houses without toilets had significantly higher reinfection rates than others at 3 months (P < 0.05). At 6 months, maternal employment status emerged as another predictor where children of working mothers had significantly higher reinfection rates (P = 0.026). In conclusion, reinfection rate of STH is high and thus necessitates frequent and periodic deworming among children. Public health personnel need to re-look at the current control measures and identify innovative and integrated ways in order to reduce STH significantly in the rural communities. (C) 2008 Elsevier B.V. All rights reserved.